2021
DOI: 10.1111/lnc3.12412
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering during reading: An interdisciplinary and integrative review of psychological, computing, and intervention research and theory

Abstract: A large proportion of thoughts are internally generated.Of these, mind wandering-when attention shifts away from the current activity to an internal stream of thought-is frequent during reading and is negatively related to comprehension outcomes. Our goal is to review research on mind wandering during reading with an interdisciplinary and integrative lens that spans the cognitive, behavioural, computing and intervention sciences. We begin with theoretical developments on mind wandering, both in general and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 149 publications
(207 reference statements)
0
6
1
Order By: Relevance
“…Notably, the strength of the association found in the present study mirrors that found in a previous meta-analysis (i.e., −0.24) conducted to assess the relationship between MW and adults’ performance in a wide set of cognitive tasks other than RC (e.g., interference control, sustained attention, visual search; Randall et al, 2014 ). On the counterpart, it was lower than what was found by D’Mello and Mills ( 2021 ), who merged results from their lab with those on reading reported in Randall et al’s study that resulted in a correlation of r = −.31.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Notably, the strength of the association found in the present study mirrors that found in a previous meta-analysis (i.e., −0.24) conducted to assess the relationship between MW and adults’ performance in a wide set of cognitive tasks other than RC (e.g., interference control, sustained attention, visual search; Randall et al, 2014 ). On the counterpart, it was lower than what was found by D’Mello and Mills ( 2021 ), who merged results from their lab with those on reading reported in Randall et al’s study that resulted in a correlation of r = −.31.…”
Section: Discussioncontrasting
confidence: 50%
“…To date, there are no meta-analyses that systematically investigated the strength of the association between MW and RC as well as explored the influence of relevant intervening factors on such a relationship. Recently, D’Mello and Mills ( 2021 ) reported on a mini-meta-analysis combing results from the reading results in Randall et al’s ( 2014 ) study and 25 effects from studies conducted in their lab. They found a weighted mean correlation between MW and RC of −0.31.…”
Section: Introductionmentioning
confidence: 99%
“…According to , vocal production can provide a boost to memory that helps with rote memorization and facilitates deeper processing. Besides, reading aloud can effectively prevent mind wandering (Varao Sousa et al, 2013), which is common during reading and has a negative association with comprehension (D'Mello & Mills, 2021). For those reasons, one might assume that reading aloud can facilitate incidental collocation learning, which requires empirical research to be conducted.…”
Section: Input Modality and Incidental Collocation Learningmentioning
confidence: 99%
“…The text-driven bottom-up process is as important when measuring the comprehensibility of texts as are the cognitive features, targets and interests of the readers themselves (Schraw and Dennison, 1994;Neiles, 2012;Ho et al, 2014). Readers' linking of information and their own mental structures lead to an in-depth processing of the content, so that the reader is able to construct and re-construct textual and non-textual information (Kintsch and van Dijk, 1978;D'Mello and Mills, 2021).…”
Section: Comprehensibility Researchmentioning
confidence: 99%